2020
DOI: 10.1186/s12886-020-01683-8
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study to evaluate visual function endpoints in non-advanced age-related macular degeneration

Abstract: Background To prevent irreversible vision loss in age-related macular degeneration (AMD), it is critical to detect retinal dysfunction before permanent structural loss occurs. In the current study we evaluated a series of visual function tests to identify potential endpoints to detect visual dysfunction in non-advanced AMD. Methods A series of visual function tests were performed on 23 non-advanced AMD subjects (AREDS grade 1–4 on si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Though higher than AUC values presented here, both studies demonstrated greatest discrimination with CS, followed by LLVA, MAT, BCVA, and IReST in decreasing order. Narayanan et al also explored the discriminatory power of BCVA, LLVA, and CS between individuals with no AMD and those with nonadvanced AMD (AREDS grade, 1-4 on a simplified scale). Again, best discrimination was achieved with CS, with BCVA and LLVA failing to offer any discriminatory power.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though higher than AUC values presented here, both studies demonstrated greatest discrimination with CS, followed by LLVA, MAT, BCVA, and IReST in decreasing order. Narayanan et al also explored the discriminatory power of BCVA, LLVA, and CS between individuals with no AMD and those with nonadvanced AMD (AREDS grade, 1-4 on a simplified scale). Again, best discrimination was achieved with CS, with BCVA and LLVA failing to offer any discriminatory power.…”
Section: Discussionmentioning
confidence: 99%
“…This report focuses on a subset of the chosen VF end points that are chart based and arguably the simplest and least burdensome to capture, namely BCVA, low-luminance visual acuity (LLVA), Moorfields Acuity Test (MAT), Pelli-Robson Contrast Sensitivity (CS), and International Reading Speed Test (IReST) . Under single-center, cross-sectional settings, all 5 chart-based tests have previously demonstrated a statistically significant reduction in visual function in participants with iAMD compared with age-similar healthy individuals . Whether this holds in large, multicenter investigations and whether they can track change over time remains to be seen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the most advanced stage, the patient's vision can be threatened by the progression of geographic atrophy involving the centre of the macula or the presence of macular neovascularization. Prior to stage 4, visual acuity is often not affected and cannot be used as a marker of disease progression (Narayanan et al, 2020). However, other functional tests can be performed, such as colour vision, low luminance visual acuity or contrast sensibility (Cocce et al, 2018; Pondorfer et al, 2020), but the lack of standards and reproducibility between centres limits the use of these tests in clinical practice (Hernández‐Andrés et al, 2020; Patel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…And then treated control group with rosuvastatin calcium tablets (5 mg, orally, once a day) and calcium dobesilate capsules (0.5 g, orally, three times a day); As well as receiving the same drugs as control group and observation group also received minocycline (100 mg; orally; every 12 h). The treatment cycle is 60 d. The change in visual acuity score relative to the baseline in the Early Treatment Diabetic Retinopathy Study (ETDRS) letters of the two groups after treatment [13] , is divided into the markedly effective, the effective and the ineffective. The markedly effective: After treatment, the visual acuity is improved more than 2 lines by visual inspection; Effective: The visual acuity is improved more than 1 line; Invalid: The visual acuity, microangioma and fundus oozing blood remain unchanged or even sharpened.…”
mentioning
confidence: 99%